Proving of Predicate Crimes in Cases of Money Laundering Crimes - Muchtar, Musdayanti; Asis, Abd.; Muin, Audyna Mayasari (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to analyze the application of law in UURI No. 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes in proving predicate crimes. The research was carried out using normative juridical research methods using statutory and case approaches. The results of the study show that in the application of Article 69 to the crime of money laundering in the decision, namely Decision Number 43/Pid.Sus/2017/PN.Bir with the defendant Murtala Ilyas Bin Ilyas, has used Article 69 because there was no previous decision related to the predicate crime. As for some of the obstacles experienced in the application of Article 69, namely the potential for the accused to be free from legal bondage, the lack of certain facilities and amenities, and the potential for violating the principle of the presumption of innocence.